The crystal structure of scapolite in the Luetzow-Holm Bay region, East Antarctica - Yamakawa,Junji; Ando,Yumi; Osanai,Yasuhito; Kusachi,Isao (National Institute of Polar Research, 2001)
P(論文) The crystal structure of scapolite from the Liitzow-Holm Bay region, East Antarctica with cell formular (Na_<1.97>Ca_<1.48>K_<0.46>Mg_<0.03>) _<3.94> (Al_<4.15>Si_<7.85>Fe_<0.01>) _<12.01>O_<24.00> (Cl_<0.65>(CO_3) _<0.42>) _<1.07>, Me_<39>, was determined in tetragonal, P4_2/n, a=12.122(2); c=7.585(2) A by the single crystal X-ray diffraction method. The structure is the same as that of meionite but with some difference in atomic coordinates and Al percentage in the tetrahedon. The CO_3 groups were mainly disordered on the xy plane and off-centred from the Anion site. The cation site was 8-coordinate rather than 6-coordinate. departmental bulletin paper